Titanium alloy surface strengthening wear-resistant layer and preparation method thereof

By coating zirconia, rare earth zirconate and zirconium oxide layers on the surface of the titanium alloy in turn, and using laser cladding technology to form a metal-based wear-resistant layer with diffuse distribution of spherical rare earth zirconate particles, the problems of insufficient wear resistance and poor interface bonding force on the surface of the titanium alloy are solved, and a wear-resistant layer with high wear resistance and toughness are achieved.

CN119592946AActive Publication Date: 2025-03-11AVIC BEIJING INST OF AERONAUTICAL MATERIALS

Patent Information

Application Number
CN202411789751.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The surface wear resistance of titanium alloy is insufficient, the existing hard ceramic layer is highly brittle, while the interface bonding force between the metal-ceramic composite coating prepared by electrodeposition and the titanium alloy is poor.

Method used

A multi-layer coating method of rare earth zirconate and zirconium oxide is used, combined with laser cladding technology, a metal-based wear-resistant layer with diffuse distribution of spherical rare earth zirconate particles is formed.

Benefits of technology

The complete fusion and metallurgical combination of the titanium alloy surface wear-resistant layer and the substrate is achieved, avoiding the problem of poor interfacial bonding force, and at the same time, it has the wear resistance of ceramics and the high toughness of metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592946A_ABST
    Figure CN119592946A_ABST
Patent Text Reader

Abstract

The invention relates to a titanium alloy surface strengthened wear-resistant layer and a preparation method thereof, and belongs to the technical field of wear-resistant coatings. The preparation method comprises the following steps: S1, preparing rare earth zirconate slurry and zirconium oxide slurry; s2, the surface of the titanium alloy is sequentially coated with zirconium oxide slurry, rare earth zirconate slurry and zirconium oxide slurry and dried, and bottom layer zirconium oxide, a rare earth zirconate layer and top layer zirconium oxide are formed on the surface of the titanium alloy; and S3, the dried surface of the titanium alloy is coated with laser scanning, so that the bottom zirconium oxide layer, the rare earth zirconate layer and the top zirconium oxide layer are clad on the surface of the titanium alloy, and the metal-based wear-resistant layer with rare earth zirconate spherical particles distributed in a dispersed mode is formed. The wear-resistant layer is prepared on the surface of the titanium alloy through laser cladding, the problem of poor interface bonding force between the wear-resistant layer and the titanium alloy does not exist, and the wear-resistant layer has wear resistance and enough toughness due to the spherical strengthening phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wear-resistant coatings, in particular to a titanium alloy surface strengthening wear-resistant layer and a preparation method thereof. Background Art

[0002] Titanium metal and its alloys have relatively low density, high specific strength and excellent corrosion resistance, and are widely used in many industrial fields such as aviation, aerospace, and navigation. However, a major performance defect of titanium alloy is its insufficient surface wear resistance. In actual working conditions, it is easy to suffer from micro-wear and abrasive wear, which not only causes mechanical damage to the surface of titanium alloy, but also destroys the protective passivation film on the surface, leading to an accelerated corrosion rate.

[0003] Preparing a wear-resistant coating on the surface of titanium alloy by various means, such as spraying, laser cladding, electroplating, etc., is an effective method to improve the friction performance of titanium alloy. At present, the wear-resistant coating used in most cases is a hard ceramic layer, which has high hardness and good wear resistance, but also has great brittleness and is prone to cracking and peeling. Metal-ceramic composite coatings can take into account the wear resistance and toughness of the coating, and are generally prepared by a composite electrodeposition method. However, titanium alloys are difficult to electroplate metals, and the interface bonding strength between the coating prepared by the composite electrodeposition process and the substrate is difficult to guarantee. Summary of the invention

[0004] In view of the above analysis, an embodiment of the present invention aims to provide a titanium alloy surface strengthening wear-resistant layer and a preparation method thereof, so as to solve the problem that the existing hard ceramic layer is brittle and the high-toughness metal-ceramic composite coating prepared by electrodeposition has poor interface bonding with the titanium alloy.

[0005] On the one hand, an embodiment of the present invention provides a method for preparing a titanium alloy surface strengthening wear-resistant layer, comprising:

[0006] Step S1, preparing rare earth zirconate slurry and zirconium oxide slurry;

[0007] Step S2, coating zirconium oxide slurry, rare earth zirconate slurry and zirconium oxide slurry on the surface of the titanium alloy in sequence and drying them to form a bottom layer of zirconium oxide, a rare earth zirconate layer and a top layer of zirconium oxide on the surface of the titanium alloy;

[0008] Step S3, using laser scanning to coat the dried titanium alloy surface, so that the bottom zirconium oxide layer, the rare earth zirconate layer and the top zirconium oxide layer are clad on the titanium alloy surface to form a metal-based wear-resistant layer with spherical rare earth zirconate particles dispersed.

[0009] Further, in step S2, the coating amount of rare earth zirconate is controlled to be 0.2 g / cm 2 ~0.3g / cm 2 .

[0010] Furthermore, in step S2, the coating amount of the bottom layer of zirconium oxide is controlled to be 1 / 2 of the coating amount of the rare earth zirconate.

[0011] Furthermore, in step S3, when laser scanning is used to coat the dried titanium alloy surface, the laser power is controlled at 600W to 800W, and the laser scanning rate is controlled at 1800mm / min to 2000mm / min.

[0012] Further, in step S2, the coating amount of the top layer of zirconium oxide is controlled to be 0.1 g / cm 2 ~0.2g / cm 2 .

[0013] Furthermore, in step S1, rare earth zirconate powder is uniformly mixed with a solvent to prepare rare earth zirconate slurry; zirconium oxide powder is uniformly mixed with a solvent to prepare zirconium oxide slurry.

[0014] Furthermore, the particle size of the rare earth zirconate powder is controlled to be 5 to 10 μm.

[0015] Furthermore, the particle size of the zirconium oxide powder is controlled to be 30 to 50 μm.

[0016] Further, in step S3, the laser is controlled to scan along a serpentine reciprocating scanning route, and the overlap between adjacent passes is 40% to 60%.

[0017] On the other hand, an embodiment of the present invention provides a reinforced wear-resistant layer on the surface of a titanium alloy, which is formed by laser cladding using the method of the above embodiment. The reinforced wear-resistant layer includes: a metal matrix clad on the surface of the titanium alloy and spherical rare earth zirconate particles dispersed in the matrix.

[0018] Compared with the prior art, the present invention can at least achieve the following beneficial effects:

[0019] 1. The present invention prepares a wear-resistant layer on the surface of a titanium alloy by laser cladding. The laser-clad wear-resistant layer and the titanium alloy are completely metallurgically bonded, and there is no problem of poor interface bonding strength. In addition, the prepared metal-based wear-resistant layer reinforced with spherical rare earth zirconate ceramic particles has both the wear resistance of ceramics and the high toughness of metals, thereby ensuring the interface bonding strength and wear resistance of the wear-resistant layer while giving the wear-resistant layer sufficient toughness.

[0020] 2. The present invention sequentially coats three layers of slurry, namely, bottom zirconium oxide, rare earth zirconate, and top zirconium oxide, on the surface of the titanium alloy. During the laser cladding process, the zirconium element can be supplemented by the bottom zirconium oxide and the top zirconium oxide to compensate for the serious burning of the zirconium element by the rare earth zirconate during the laser cladding process. The zirconium element of the lower layer is protected by the top zirconium oxide to reduce the loss of the zirconium element of the lower layer, thereby ensuring that rare earth zirconate rather than rare earth oxide is formed in the final cladding layer.

[0021] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0023] Figure 1 This is a diagram of the organizational structure of the cross section of the wear-resistant layer on the surface of the titanium alloy in Example 1 of the present invention.

[0024] Figure 2 This is a diagram of the organizational structure of the cross section of the wear-resistant layer on the surface of the titanium alloy of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0026] An embodiment of the present invention provides a method for preparing a wear-resistant layer on the surface of a titanium alloy, comprising:

[0027] Step S1, preparing rare earth zirconate slurry and zirconium oxide slurry;

[0028] Step S2, coating zirconium oxide slurry, rare earth zirconate slurry and zirconium oxide slurry on the surface of the titanium alloy in sequence and drying them to form a bottom layer of zirconium oxide, a rare earth zirconate layer and a top layer of zirconium oxide on the surface of the titanium alloy;

[0029] Step S3, using laser scanning to coat the dried titanium alloy surface, so that the bottom zirconium oxide layer, the rare earth zirconate layer and the top zirconium oxide layer are clad on the titanium alloy surface to form a metal-based wear-resistant layer dispersed with rare earth zirconate.

[0030] The present invention prepares a reinforced wear-resistant layer on the surface of a titanium alloy by laser cladding. The metal-based wear-resistant layer clad by laser cladding is completely metallurgically bonded to the titanium alloy, and there is no problem of poor interface bonding strength. In addition, the present invention prepares a metal-based wear-resistant layer by laser cladding, and spherical rare earth zirconate ceramic particles are dispersedly distributed in the metal-based wear-resistant layer, so that the wear-resistant layer has both the wear resistance of ceramics and the high toughness of metals. Therefore, the method of the present invention is used to prepare a wear-resistant layer on the surface of a titanium alloy, while ensuring the interface bonding strength and wear resistance of the wear-resistant layer, it can also give the wear-resistant layer sufficient toughness.

[0031] The chemical formula of rare earth zirconate is RE2Zr2O7, wherein RE is any one or a combination of at least two of rare earth elements, for example, any one or a combination of at least two of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, scandium, yttrium, etc. For example: La2Zr2O7, Ce2Zr2O7, Sm2Zr2O7, Lu2Zr2O7, (Y 0.5 La 0.5 )2Zr2O7、(Y 0.3 La 0.3 Nd 0.2 Sm 0.2 )2Zr2O7, etc.

[0032] Since zirconium element is easily lost in the form of zirconium vapor during the laser cladding process, and the burning loss is relatively serious, the present invention arranges a top layer of zirconium oxide and a bottom layer of zirconium oxide above and below the rare earth zirconate layer respectively, and uses zirconium oxide to additionally supplement the zirconium element. In the laser cladding process, the bottom layer of zirconium oxide and the top layer of zirconium oxide can compensate for the serious burning loss of zirconium element in the rare earth zirconate during the laser cladding process. At the same time, the top layer of zirconium oxide protects the zirconium element in the lower layer, reduces the loss of the zirconium element in the lower layer, and ensures that rare earth zirconate rather than rare earth oxide is formed in the final cladding layer.

[0033] In some embodiments, in step S1, rare earth zirconate powder is uniformly mixed with a solvent to prepare a rare earth zirconate slurry; zirconium oxide powder is uniformly mixed with a solvent to prepare a zirconium oxide slurry.

[0034] In some embodiments, the solvent used may be acetone. The mass ratio of rare earth zirconate powder to acetone may be controlled within the range of 1:1 to 1.5:1, and the mass ratio of zirconium oxide powder to acetone may also be controlled within the range of 1:1 to 1.5:1.

[0035] In some embodiments, in step S1, the particle size of the rare earth zirconate powder is controlled to be 5 to 10 μm. If the particle size of the rare earth zirconate powder is too small, the specific surface area of ​​the powder is too high, which will aggravate the burning of zirconium elements during the cladding process; if the particle size of the rare earth zirconate powder is too large, the surface after cladding will be too rough.

[0036] In some embodiments, the particle size of the zirconium oxide powder used in step S1 is controlled to be 30-50 μm. The relatively large particle size of the zirconium oxide powder is used to make the top zirconium oxide coating layer denser, to strengthen the protection of the underlying zirconium element, and to reduce the burning loss of the underlying zirconium element.

[0037] In some embodiments, the coating amount of rare earth zirconate can be controlled to be 0.2 g / cm 2 ~0.3g / cm 2 , for example, 0.2 g / cm 2 , 0.21g / cm 2 , 0.22g / cm 2 , 0.23g / cm 2 , 0.24g / cm 2 , 0.25g / cm 2 , 0.26g / cm 2 , 0.27g / cm 2 , 0.28g / cm 2 , 0.29g / cm 2 , 0.3g / cm 2 The present invention controls the coating amount of rare earth zirconate to ensure that the formed wear-resistant layer has dispersed rare earth zirconate particles to enhance the wear resistance of the wear-resistant layer and avoid poor wear resistance due to excessive or insufficient coating amount of rare earth zirconate.

[0038] In some embodiments, in step S2, the coating amount of the bottom zirconia can be determined according to the coating amount of the rare earth zirconate. Specifically, the coating amount of the bottom zirconia can be controlled to be 1 / 2 of the coating amount of the rare earth zirconate. During the laser cladding process, both the bottom zirconia and the rare earth zirconate layer will be melted into the titanium alloy matrix in large quantities to form a titanium zirconium metal-based cladding layer, while some rare earth zirconate particles are dispersed in the metal-based cladding layer.

[0039] Among them, the relative content between the bottom zirconia layer and the rare earth zirconate layer will affect the composition structure of the cladding layer. If the bottom zirconia coating amount is too low, the zirconium element burnout in the rare earth zirconate cannot be fully replenished during the laser cladding process, which may cause a large amount of rare earth oxides in the wear-resistant layer instead of complete rare earth zirconates; if the bottom zirconia coating amount is too high, a large amount of zirconium oxide may exist in the wear-resistant layer instead of complete rare earth zirconates, thereby affecting the wear resistance of the wear-resistant layer.

[0040] In step S2, after each layer of slurry is coated, it should be dried naturally in the air for a period of time, for example, 5 to 8 minutes, to ensure that three coating layers of top and bottom zirconium oxide, rare earth zirconate layer and top zirconium oxide are finally formed.

[0041] In some embodiments, in step S3, when laser scanning is used to coat the dried titanium alloy surface, the laser power is controlled at 600-800W, for example, 600W, 650W, 700W, 750W, 800W; the laser scanning rate is controlled at 1800-2000mm / min, for example, 1800mm / min, 1850mm / min, 1900mm / min, 1950mm / min, 2000mm / min. During the laser cladding process, the laser power and scanning rate determine the heat input of the laser. If the laser power is too large or the scanning rate is too low, the heat input will be too high, resulting in too high a degree of mixed melting between the coating layer and the titanium alloy, and too large a melting depth of the titanium alloy, which will lead to a low content of rare earth zirconate particles in the wear-resistant layer, and an effective strengthening effect cannot be achieved. On the contrary, if the heat input is too small, the coating layer cannot be fused with the titanium alloy, and a wear-resistant layer with a uniform organizational structure cannot be formed.

[0042] In some embodiments, the coating amount of the top layer of zirconium oxide can be controlled to be 0.1 g / cm 2 ~0.2g / cm 2 , for example, 0.1 g / cm 2 , 0.11g / cm 2 , 0.12g / cm 2 , 0.13g / cm 2 , 0.14g / cm 2 , 0.15g / cm 2 , 0.16g / cm 2 , 0.17g / cm 2 , 0.18g / cm 2 , 0.19g / cm 2 , 0.2g / cm 2 If the coating amount is too much, zirconium oxide will remain on the surface of the cladding layer; if the coating amount is too small, it will not be able to provide good protection for the lower layer, resulting in more zirconium being burned under the action of the laser. The present invention can ensure good protection for the lower layer by controlling the coating amount of the top layer of zirconium oxide, while avoiding residual zirconium oxide in the formed wear-resistant layer.

[0043] It should be noted that the main function of the top layer of zirconia is to protect the zirconium elements of the two layers below it from loss as little as possible, so its coating amount has nothing to do with the coating amount of the two layers below it. The present invention controls the coating amount of the top layer of zirconia mainly to ensure that there is no obvious residue during the laser cladding process, and to protect the zirconium elements of the lower layer from serious burning.

[0044] Therefore, the coating amount of the top layer of zirconia is mainly related to the heat input of the laser used, that is, the specific coating amount of the top layer of zirconia can be determined according to the power and scanning rate of the laser. When the laser power is small or the scanning rate is high, a smaller coating amount of the top layer of zirconia should be used; when the laser power is large or the scanning rate is low, a larger coating amount of the top layer of zirconia should be used. When the required laser power in the laser cladding process is 600-800W and the laser scanning rate is 1800-2000mm / min, the coating amount of the top layer of zirconia can be controlled to 0.1g / cm 2 ~0.2g / cm 2 .

[0045] In some embodiments, during the laser cladding process of step S3, a serpentine reciprocating scanning route is used to control the laser scanning, and the overlap between adjacent passes is 40% to 60%, preferably 50%.

[0046] In some embodiments, after step S3 is completed, it also includes: cleaning residual powder on the surface of the titanium alloy to remove impurities and pollutants generated during the laser cladding process to ensure the quality and performance of the wear-resistant layer.

[0047] The embodiment of the present invention also provides a reinforced wear-resistant layer on the surface of a titanium alloy. The reinforced wear-resistant layer comprises: a metal matrix clad on the surface of the titanium alloy and spherical rare earth zirconate particles dispersed in the matrix. The wear-resistant layer can be formed by laser cladding using the method of the above embodiment.

[0048] The wear-resistant layer of the embodiment of the present invention is a metal matrix reinforced with spherical rare earth zirconate particles. The wear-resistant layer with metal as the matrix has higher toughness than hard ceramics. A large number of spherical rare earth zirconate particles are dispersed in the metal matrix, which can enhance the wear resistance of the metal matrix, so that the wear-resistant layer of the present invention has both high toughness and wear resistance.

[0049] The titanium alloy surface strengthening wear-resistant layer and the preparation method thereof of the present invention are further described below using examples.

[0050] Example 1

[0051] The method for preparing the titanium alloy surface strengthening and wear-resistant layer of this embodiment includes the following steps.

[0052] (1) Cut a Ti60 titanium alloy plate with a size of 30 mm × 30 mm × 3 mm, and clean and degrease the surface.

[0053] (2) According to the mass ratio of acetone to powder of 1:1, paste slurries of lanthanum zirconate and zirconium oxide were prepared respectively. The average particle size of the selected lanthanum zirconate was 5 μm, and the average particle size of the selected zirconium oxide was 30 μm.

[0054] (3) Coat 0.1g / cm on the surface of Ti60 sheet 2 The bottom zirconium oxide layer, 0.2g / cm 2 Lanthanum zirconate layer and 0.1g / cm 2 That is, 0.9 g of zirconium oxide was coated on one side and dried naturally for 8 minutes; then 1.8 g of lanthanum zirconate was coated and dried naturally for 8 minutes; finally, 0.9 g of zirconium oxide was coated and dried naturally for another 8 minutes.

[0055] (4) The laser power was set to 600 W, the scanning rate was set to 2000 mm / min, the scanning route was set to serpentine reciprocating along the edge of the Ti60 titanium alloy plate, the overlap between adjacent passes was set to 50%, and a laser cladding process was performed.

[0056] (5) Clean the residual powder on the surface.

[0057] The organizational structure of the final wear-resistant layer cross section is observed, such as Figure 1 As shown in the figure, the depth of the wear-resistant layer (i.e., the cladding layer) is about 510 μm, in which a large number of fine spherical particles are distributed. EDS detection shows that the composition of the spherical particles dispersed in the wear-resistant layer includes 70.5 at.% O, 14.8 at.% Zr, 12.6 at.% La and 2.1 at.% Ti, and it is judged that the spherical particles are mainly lanthanum zirconate.

[0058] The wear resistance test of the titanium alloy plate with the wear-resistant layer was carried out. Under the test conditions of 10N pressure and 10min of reciprocating friction, the wear amount of the sample in this embodiment was about 9.8mg.

[0059] Example 2

[0060] The method for preparing the titanium alloy surface strengthening and wear-resistant layer of this embodiment includes the following steps.

[0061] (1) Cut a Ti60 titanium alloy plate with a size of 30 mm × 30 mm × 3 mm, and clean and degrease the surface.

[0062] (2) According to the mass ratio of acetone to powder of 1:1.5, yttrium zirconate and zirconium oxide paste slurries were prepared respectively. The average particle size of the selected yttrium zirconate was 8 μm, and the average particle size of the selected zirconium oxide was 50 μm.

[0063] (3) Coat 0.1g / cm on the surface of Ti60 sheet 2 The bottom zirconium oxide layer, 0.2g / cm 2 Yttrium zirconate layer and 0.1g / cm 2That is, 0.9g of zirconium oxide was coated on one side of the Ti60 plate and dried naturally for 5 minutes; then 1.8g of yttrium zirconate was coated and dried naturally for 5 minutes; finally, 0.9g of zirconium oxide was coated and dried naturally for 5 minutes.

[0064] (4) The laser power was set to 800 W, the scanning rate was set to 1800 mm / min, the scanning route was set to serpentine reciprocating along the edge of the Ti60 titanium alloy plate, the overlap between adjacent passes was set to 50%, and a laser cladding process was performed.

[0065] (5) Clean the residual powder on the surface.

[0066] The wear resistance test of the titanium alloy plate with the wear-resistant layer was carried out. Under the test conditions of 10N pressure and 10min of reciprocating friction, the wear loss of the sample of this embodiment was about 11.7mg.

[0067] Example 3

[0068] The method for preparing the titanium alloy surface strengthening and wear-resistant layer of this embodiment includes the following steps.

[0069] (1) Cut a Ti60 titanium alloy plate with a size of 30 mm × 30 mm × 3 mm, and clean and degrease the surface.

[0070] (2) According to the mass ratio of acetone to powder of 1:1.2, paste slurries of samarium zirconate and zirconium oxide were prepared respectively. The average particle size of the selected lanthanum zirconate was 10 μm, and the average particle size of the selected zirconium oxide was 40 μm.

[0071] (3) Coat 0.1g / cm on the surface of Ti60 sheet 2 The bottom zirconium oxide layer, 0.2g / cm 2 The samarium zirconate layer and 0.1g / cm 2 That is, 0.9g of zirconium oxide was coated on one side and dried naturally for 7 minutes; then 1.8g of samarium zirconate was coated and dried naturally for 7 minutes; finally, 0.9g of zirconium oxide was coated and dried naturally for 7 minutes.

[0072] (4) The laser power was set to 700 W, the scanning rate was set to 1900 mm / min, the scanning route was set to serpentine reciprocating along the edge of the Ti60 titanium alloy plate, the overlap between adjacent passes was 50%, and a laser cladding process was performed.

[0073] (5) Clean the residual powder on the surface.

[0074] The wear resistance test of the titanium alloy plate with the wear-resistant layer was carried out. Under the test conditions of 10N pressure and 10min of reciprocating friction, the wear amount of the sample in this embodiment was about 10.5mg.

[0075] Example 4

[0076] The difference between this embodiment and embodiment 1 is that the rare earth zirconate coated on the surface of the titanium alloy plate in this embodiment contains a combination of two rare earth elements. Specifically, the rare earth zirconate is replaced by (Y 0.5 La 0.5 )2Zr2O7, and the other conditions are the same as in Example 1.

[0077] Under the reciprocating friction test conditions of 10N pressure and 10min, the wear amount of the sample in this embodiment is about 9.1mg.

[0078] Example 5

[0079] In order to explore the effect of different coating amounts of each coating layer on the wear resistance, 9 identical Ti60 titanium alloy plates with a size of 30 mm × 30 mm × 3 mm were prepared, recorded as samples 1 to 9; zirconia slurry, lanthanum zirconate slurry and zirconia slurry were coated on the surface of each sample in turn, and the coating amount of each layer of slurry is shown in Table 1.

[0080] The remaining conditions are the same as those in Example 1 and will not be described in detail here.

[0081] The wear resistance of each sample was tested. Under the conditions of 10N pressure and 10min reciprocating friction test, the wear amount of each sample is shown in Table 1.

[0082] Table 1 Coating amount of different coating layers and corresponding wear resistance of wear-resistant layer

[0083]

[0084] According to the wear resistance test results of samples 1 to 5 in Table 1, when the coating amount of the lanthanum zirconate layer and the coating amount of the bottom zirconium oxide are within the appropriate range, the sample wear amount is low, below 13.6 mg, and the wear resistance is significantly improved. When the coating amount of lanthanum zirconate is too little or too much, see sample 1 and sample 5, the wear amount of the sample increases significantly, indicating that its wear resistance is deteriorated.

[0085] According to the wear resistance test results of samples 2, 6 to 9 in Table 1, when the coating amount of the top layer of zirconia is in the appropriate range (0.1 to 0.2 g / cm 2 ), the wear amount of the sample is low, below 11.5 mg, and the wear resistance is significantly improved. When the coating amount of the top layer of zirconia is too little or too much, see Samples 6 and 9, the wear amount of the sample increases significantly, indicating that its wear resistance is deteriorated.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that this comparative example only coats a layer of 0.2 g / cm2 Lanthanum zirconate, that is, coating 1.8 g of lanthanum zirconate on one side and drying naturally for 8 minutes.

[0088] The structure of the formed wear-resistant layer cross section is observed, such as Figure 2 As shown, the depth of the wear-resistant layer (i.e., cladding layer) is about 680 μm. Compared with Example 1, the titanium alloy plate of this comparative example is subjected to a greater thermal impact and melts to a greater extent; a large number of fine spherical particles are also distributed therein. However, according to EDS detection, the composition of the spherical particles dispersed in the wear-resistant layer includes 66.3 at.% O, 1.8 at.% Zr, 30.2 at.% La and 1.7 at.% Ti, and it is judged that the spherical particles are mainly lanthanum oxide, indicating that when the zirconium oxide layer is not coated, the zirconium element in the lanthanum zirconate layer is severely burned.

[0089] The wear resistance test of the titanium alloy plate with the wear-resistant layer was carried out. Under the conditions of 10N pressure and 10min of reciprocating friction test, the wear amount of the sample of this comparative example was about 15.5mg.

[0090] By comparing Example 1 and the present comparative example, it can be seen that by respectively arranging a top layer of zirconium oxide and a bottom layer of zirconium oxide above and below the rare earth lanthanum zirconate, the burning loss of zirconium element during the laser cladding process can be supplemented, ensuring that rare earth zirconate particles instead of rare earth oxides are formed in the wear-resistant layer, thereby significantly improving the wear resistance of the wear-resistant layer.

[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a titanium alloy surface strengthening wear-resistant layer, characterized in that: include: Step S1, preparing rare earth zirconate slurry and zirconium oxide slurry; Step S2, coating the zirconium oxide slurry, the rare earth zirconate slurry and the zirconium oxide slurry on the surface of the titanium alloy in sequence and drying them to form a bottom layer of zirconium oxide, a rare earth zirconate layer and a top layer of zirconium oxide on the surface of the titanium alloy; Step S3, using laser scanning to coat the dried titanium alloy surface, so that the bottom zirconium oxide layer, the rare earth zirconate layer and the top zirconium oxide layer are clad on the titanium alloy surface to form a metal-based wear-resistant layer with dispersed spherical rare earth zirconate particles.

2. The method according to claim 1, characterized in that In step S2, the coating amount of the rare earth zirconate is controlled to be 0.2 g / cm 2 ~0.3g / cm 2 .

3. The method according to claim 2, characterized in that In the step S2, the coating amount of the bottom layer zirconium oxide is controlled to be 1 / 2 of the coating amount of the rare earth zirconate.

4. The method according to claim 1, characterized in that: In the step S3, when laser scanning is used to coat the dried titanium alloy surface, the laser power is controlled at 600-800 W, and the laser scanning rate is controlled at 1800-2000 mm / min.

5. The method according to claim 4, characterized in that In step S2, the coating amount of the top layer of zirconium oxide is controlled to be 0.1 g / cm 2 ~0.2g / cm 2 .

6. The method according to any one of claims 1 to 5, characterized in that: In the step S1, the rare earth zirconate powder is uniformly mixed with a solvent to prepare the rare earth zirconate slurry; the zirconium oxide powder is uniformly mixed with a solvent to prepare the zirconium oxide slurry.

7. The method according to claim 6, characterized in that The particle size of the rare earth zirconate powder is controlled to be 5 to 10 μm.

8. The method according to claim 6, characterized in that The particle size of the zirconium oxide powder is controlled to be 30 to 50 μm.

9. The method according to claim 1, characterized in that: In step S3, the laser is controlled to scan along a serpentine reciprocating scanning route, and the overlap between adjacent passes is 40% to 60%.

10. A reinforced wear-resistant layer on the surface of a titanium alloy, characterized in that: The reinforced wear-resistant layer is formed by laser cladding according to the method described in any one of claims 1 to 9, and comprises: a metal matrix clad on the surface of the titanium alloy and spherical rare earth zirconate particles dispersed in the matrix.

Citation Information

Patent Citations

  • Method for laser cladding of wollastonite-based bioactive ceramic coating on surface of titanium alloy

    CN103981519A

  • Method for preparing wear-resistant and high-temperature-resistant coating on surface of titanium alloy through laser cladding

    CN113088957A

  • Ni3Al-based self-lubricating coating with multi-layer structure and preparation method of Ni3Al-based self-lubricating coating

    CN117448809A

  • Method for preparing high strength and toughness magnesium-rare earth alloy by means of selective laser melting additive manufacturing technology

    EP4029629A1

Cited By

  • Seal coating, preparation method and application

    CN120330661A

  • Method for preparing high-hardness and high-wear-resistance CNx coating on titanium alloy surface

    CN120591860A